The worst journey in the world : the graphic novel. Volume 1, Making our easting down - Airriess, Sarah (Iron Circus Comics, 2024)
A graphic novel adaptation of the classic memoir of seafaring adventure and exploration to the South Pole, originally written by Apsley Cherry-Garrard.--Publisher.